Exercise and smoking habits among Swedish postmenopausal women. Issue 3 (September 1997) - Frisk, J; Brynhildsen, J; Ivarsson, T; Persson, P; Hammar, M
Abstract : OBJECTIVE: To assess exercise habits and their relation to smoking habits and social and medical factors in postmenopausal women. METHODS: A cross-sectional study with a questionnaire to all 1324 55-56 year old women in Linköping, Sweden. RESULTS: Response rate was 85%. About a third of the women took part in some kind of quite strenuous exercise for at least one hour a week. After a quarter worked out once a week; fewer did swimming and jogging. One in four women smoked. Women who used hormone replacement therapy, who were not smoking and who had a physically light occupation more often took part in strenuous sports. Women who had been treated for malignancies or with back problems exercised to the same extent as women in the general population. CONCLUSION: About a third of the post-menopausal women exercised on a regular basis, if exercise involved in getting to and from work was not counted. Since regular physical exercise has many health benefits, more women should be encouraged to take part in regular physical exercise. Factors probably associated with level of education and general awareness of the importance of a healthy lifestyle positively influenced the likelihood of these women to be physically active on a regular basis. A previous malignant disease or current back problems did not prevent women from taking part in exercise on a regular basis.